EKSPLORASI FENOMENOLOGI PELAYANAN ICU DARI PERSPEKTIF PASIEN DAN KELUARGA DI RUMKITAL DR. WAHYU SLAMET BITUNG - Sada, Fidy Randy; Lamonge, Annastasia Sintia; Palenewen, Lucky Albertus; Sandehang, Cornelia Fransiska; Caroles, Franchiska Prastimy (Universitas Sam Ratulangi, 2026)
Background: Intensive care unit (ICU) services are complex and high-risk areas of care. Patients and their families often experience emotional distress due to clinical uncertainty and limited interaction during treatment. Objective: This study aimed to explore the experiences of patients and family members regarding ICU services at Rumkital dr. Wahyu Slamet Bitung.Methods: A qualitative study with a phenomenological approach was conducted from September to November 2025. Four participants (one patient and three family members) were recruited using purposive sampling. Data were collected through semi-structured interviews and analyzed using Colaizzi’s method to identify essential themes. Results: Seven themes emerged: emotional dynamics of intensive care, quality of care and clinical communication, family as a clinical companion, system and resource constraints, caregiver burden, social-spiritual coping and support, and expectations regarding family support. Conclusion: The experiences of patients and families in the ICU are characterized by tension between emotional vulnerability and the need for a sense of safety, strongly influenced by communication, family involvement, and system capacity. Strengthening structured communication and family-centered practices should be prioritized to improve the ICU care experience. Keywords: family; intensive care unit; patient; phenomenology